Eloquence divine : in search of God's rhetoric - Arrington, Phillip (James Clarke & Co, 2017)
""While serious studies of the Bible's rhetoric have been written for academic readers ... few have attempted to examine the persuasiveness of speeches directly assigned to the biblical 'God' that so many believe in and worship. ... Further, no critic has yet tried to analyze how this God tries to invent and develop His arguments in the Bible as it has come down to us, or how this God arranges those arguments, or the styles He adopts to make them, and the roles memory and delivery play in His arguments. ... Eloquence Divine is one agnostic's attempt at such a study. Those in the humaniti.